High-Risk Extended-Spectrum Beta-Lactamase (blaTEM) and Metallo-Beta-Lactamase (blaNDM) Genes in Escherichia coli from Clinical Wastewater from a Nigerian Teaching Hospital: A One Health Perspective - Kelechukwu Nwancho Ogboji; Ifeoma Precious Ogbonna; Chidinma Stacy Iroha; Obinna Okpaga Awoke; Ikemesit Udeme Peter; Ifeanyichukwu Romanus Iroha (World Journal of Advanced Pharmaceutical and Life Sciences, 2026)
Background: Hospital wastewater is increasingly recognized as a critical reservoir for multidrug-resistant Gram-negative bacteria, contributing to the global antimicrobial resistance crisis. Escherichia coli harboring extended-spectrum beta-lactamase (ESBL) and metallo-beta-lactamase (MBL) genes pose significant public health threats, particularly in resource-limited settings where wastewater treatment is inadequate. However, comprehensive data on the molecular characterization of these resistance determinants from clinical wastewater in southeastern Nigeria remain scarce. Objective: This study aimed to molecularly characterize ESBL (blaTEM) and MBL (blaNDM) genes in Escherichia coli isolated from clinical wastewater at Alex Ekwueme Federal University Teaching Hospital, Abakaliki, Nigeria. Methods: A total of 30 effluent samples (500 mL each) were collected from clinical wastewater lines (CWL) of Alex Ekwueme Federal University Teaching Hospital, Abakaliki. Bacterial isolation and identification were performed using standard microbiological techniques. Antibiotic susceptibility testing was conducted using the Kirby-Bauer disk diffusion method, and Multiple Antibiotic Resistance (MAR) indices were calculated. Molecular characterization of blaTEM and blaNDM genes was performed by Polymerase Chain Reaction (PCR) using specific primers on all 40 isolated E. coli isolates. Results: E. coli was isolated from all sampling points, accounting for 40 (18.5%) of total bacterial isolates. All E. coli isolates exhibited high resistance to aztreonam (100%), ceftriaxone (97.5%), colistin (95.0%), and nalidixic acid (97.5%), while gentamicin (100%) and ciprofloxacin (87.5%) remained the most effective antibiotics. MAR indices ranged from 0.65 to 0.84, exceeding the 0.2 high-risk threshold. Molecular analysis revealed blaTEM and blaNDM genes in all 40 (100%) E. coli isolates, confirming the genetic basis for observed resistance patterns. Conclusion: This study provides the first molecular evidence of alarmingly high prevalence of E. coli co-harboring blaTEM and blaNDM genes in hospital wastewater from Abakaliki, Nigeria. The high MAR indices confirm hospital effluent as a high-risk source for antimicrobial resistance dissemination. These findings underscore the urgent need for on-site wastewater treatment interventions, enhanced antimicrobial stewardship, and integrated One Health surveillance to prevent environmental and community transmission of these multidrug-resistant pathogens.